The Fishery and Oceanography Observing System (FOOS): a tool for oceanography and fisheries science. (12th February 2016) - Patti, B.; Martinelli, M.; Aronica, S.; Belardinelli, A.; Penna, P.; Bonanno, A.; Basilone, G.; Fontana, I.; Giacalone, G.; Gabriele Gallì, N.; Sorgente, R.; Angileri, I.V.M.; et al.
ABSTRACT: The National Research Council of Italy (CNR) has been undertaking scientific and technological activities aimed at implementing intelligent and automated systems for the collection of data in support of oceanography and fisheries science, as well as providing services for fishing operators. Two independent operational units autonomously developed two original devices, the Fishery Observing System (FOS) and the Information and Communications Technology kit (ICT-kit), recently converging towards a new modular system named the Fishery and Oceanography Observing System (FOOS) that can be adapted to fit the specific research needs of the areas in which it is used. This paper reports the development process and describes the two applications in use in Italy.